Analysis of the coupled dynamics of an offshore floating multipurpose platform : part B - Hydro-elastic analysis with flexible support platform - Ruzzo, C.; Failla, G.; Arena, F.; Collu, M.; Li, L.; Mariotti, A. (Volume 6: Ocean Space Utilization, 2019)
A multi-purpose platform (MPP) is an offshore system designed to serve the purposes of more than one offshore industry. Indeed, over the past decades, a number of industries have expanded, or are expanding, from onshore to offshore locations (renewables, aquaculture, tourism, mineral extractions, etc), and the research on these type of platform is increasing. In the present work, a MPP able to accommodate wind turbines, wave energy converters, and aquaculture systems is considered. For an overview of the MPP platform considered and its research context, please refer to the EU H2020 project overview (OMAE 2019-96104). This work presents the second part (Part B) of the analyses of the dynamics of the floating support structure for this MPP, focusing on the hydro-elastic analysis, while its complementary rigid-body hydrodynamic analysis is presented in Part A (OMAE2019-96212). The aim here is to assess if the support platform structural elasticity has a substantial impact on the dynamic response of the platform. A beam model and a 3D solid model of the support structure have been developed, and the inertial forces, hydrodynamic added mass forces, hydrostatic and mooring restoring forces have been considered in the hydro-elastic analyses performed. The results show that the dynamic response to the wave loads is not substantially influenced by the elasticity of the support structure, and that, at first approximation, a rigid-body approach is acceptable.